IMPLEMENTASI NILAI PANCASILA PADA TONGKRONGAN OLEH GENERASI Z DI KECAMATAN SIDOARJO - Krisnanda, Mikhael Ekklesia; Warsono (Kajian Moral dan Kewarganegaraan, 2024)
This research aims to analyze the implementation of Pancasila values in the social activities of Generation Z in Sidoarjo District. Generation Z, known for their technological literacy, exhibits unique characteristics in their social behavior, particularly in the context of "nongkrong" (hanging out). What began as a casual activity has evolved into a social space that influences the behavior and perspectives of the younger generation. The values of Pancasila, as the nation's foundational ideology, need to be integrated into daily activities, including during social gatherings. This study employs a qualitative approach, utilizing observations and interviews with Generation Z in several hangout spots in Sidoarjo District. The findings reveal that there are varying levels of understanding and practice of Pancasila values among Generation Z. There is a gap between theoretical knowledge of Pancasila and its application in daily life. However, some values, such as solidarity, tolerance, and mutual cooperation, are still reflected in their activities. The research also identifies that social media plays a significant role in shaping Generation Z's perceptions and behaviors regarding Pancasila. Thus, this study provides new insights into the importance of revitalizing Pancasila values among Generation Z through approaches that align with their characteristics.